Nutritional and Phytochemical Composition and Associated Health Benefits of Oat (Avena sativa) Grains and Oat-Based Fermented Food Products - Getaneh Firew Alemayehu; Sirawdink Fikreyesus Forsido; Yetenayet B. Tola; Endale Amare (The Scientific World Journal)
Oats (Avena sativa L.) are a popular functional cereal grain due to their numerous health benefits. This review article summarized the information on the chemical composition and phytonutrients of oats grown in different countries. It also reviewed recently developed fermented oat products to highlight their potential for human health. Oats have an interesting nutritional profile that includes high-quality protein, unsaturated fats, soluble fiber, polyphenolic compounds, and micronutrients. Oat grain has a unique protein composition, with globulins serving as the primary storage protein, in contrast to other cereals, where prolamins are the main storage proteins. Oats have the highest fat content of any cereal, with low saturated fatty acids and high essential unsaturated fatty acid content, which can help reduce the risk of cardiovascular diseases. Oats are a good source of soluble dietary fiber, particularly β-glucan, which has outstanding functional properties and is extremely important in human nutrition. β-Glucan has been shown to lower blood cholesterol and glucose absorption in the intestine, thereby preventing diseases such as cardiovascular injury, dyslipidemia, hypertension, inflammatory state, and type 2 diabetes. Oats also contain high concentration of antioxidant compounds. Avenanthramides, which are unique to oats, are powerful antioxidants with high antioxidative activity in humans. Recognizing the nutritional benefits of oats, oat-based fermented food products are gaining popularity as functional foods with high probiotic potential.